Resilience of the diversity of forest species in experimental areas in the eastern Brazilian Amazon (Research, Society and Development, 2021)
The objective of this work was to evaluate forest resilience, in terms of diversity, in four experimental areas in the eastern Brazilian Amazon. As a hypothesis, it is expected that the upland rainforest will recover its arboreal characteristics in a 30-year cycle. The data were collected in four areas distributed in the eastern Brazilian Amazon, being in the states of Amapá and Pará. Most of the treatments that were monitored before logging in the four areas had species loss after logging with reduced impact. After the silvicultural treatments, it was observed that the loss of species is greater, due to the deliberate removal of species that are not of economic interest for sawmills, but of great importance for the forest balance. After the accidental fire, it was found that it did not change the number of species in the treatments in which they had the greatest number of damaged plots. The similarity of the forest changes regardless of whether it has been explored or not, forest exploitation accelerates this change and each treatment has its share in this context. The forest has resilience in relation to the number of species, and it varies from 3 to 30 years after logging.